The changing role of criminal law in controlling corporate behavior - Anderson, James M.; Waggoner, Ivan (RAND, 2014)
What should be the role of the criminal law in controlling corporate behavior, and how can the execution of that role be improved? On the one hand, corporations have enormous power, and, when a corporation causes harm, there is a natural instinct to apply criminal sanctions, society's most serious expression of moral disapproval. In the wake of a harm in which a corporation had a prominent role, there are often calls for an increased use of the criminal law to tame corporate excesses. On the other hand, criminal liability has historically usually required criminal intent, a concept that applies oddly to a legal construction, such as a corporation. And more recently, critics have decried what they have termed the overcriminalization of corporate behavior, suggesting that there has been an overreliance on the use of criminal law in this context. To provide guidance to policymakers on the proper role of criminal sanctions in this context, RAND Corporation researchers (1) measure the current use of criminal sanctions in controlling corporate behavior, (2) describe how the current regime developed, and (3) offer suggestions about how the use of criminal sanctions to control corporate behavior might be improved.